Pengaruh Political Connection, Earning Management, dan Corporate Social Responsibility Terhadap Tax Avoidance dengan Corporate Governance Sebagai Pemoderasi - Mikha Btari Batubara; Hexana Sri Lastanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and find empirical evidence regarding the effect of political connection, earning management on tax avoidance moderated by corporate governance. This study uses secondary data with data collection techniques using the annual reports of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. This study used purposive sampling technique with a total sample of 100 from 20 companies. Data testing in this study used multiple linear regression analysis with panel data. Tax avoidance in this study is proxied by Book Tax Difference. The results showed that political connection and CSR variables have a positive effect on tax avoidance, earning management has a negative effect on tax avoidance, and corporate governance proxied by independent commissioners does not strengthen or weaken the relationship between political connection, earning management, and CSR on tax avoidance.